Non-uniform Estimates in the Approximation by the Irwin Law - Padvelskis, Kazimieras; Prigodin, Ruslan (Lithuanian Journal of Statistics, 2016)
We consider an approximation of a cumulative distribution function F(x) by the cumulative distributionfunction G(x) of the Irwin law. In this case, a function F(x) can be cumulative distribution functions of sums (products) ofindependent (dependent) random variables. Remainder term of the approximation is estimated by the cumulant method.The cumulant method is used by introducing special cumulants, satisfying the V. Statulevičius type condition. The mainresult is a nonuniform bound for the difference |F(x)-G(x)| in terms of special cumulants of the symmetric cumulativedistribution function F(x).
Keywords: cumulative distribution function; characteristic function; cumulants; Irwin law; generalized Rademacher random variables; nonuniform estimates